Graphic women : life narrative and contemporary comics - Chute, Hillary L. (New York ; Chichester : Columbia University Press, 2010)
"Some of the most acclaimed books of the twenty-first century are autobiographical comics by women. Aline Kominsky-Crumb is a pioneer of the autobiographical form, showing women's everyday lives, especially through the lens of the body. Phoebe Gloeckner places teenage sexuality at the center of her work, while Lynda Barry uses collage and the empty spaces between frames to capture the process of memory. Marjane Satrapi's Persepolis experiments with visual witness to frame her personal and historical narrative, and Alison Bechdel's Fun Home meticulously incorporates family documents by hand to re-present the author's past. These five cartoonists move the art of autobiography and graphic storytelling in new directions, particularly through the depiction of sex, gender, and lived experience. Hillary L. Chute explores their verbal and visual techniques, which have transformed autobiographical narrative and contemporary comics. Through the interplay of words and images, and the counterpoint of presence and absence, they express difficult, even traumatic stories while engaging with the workings of memory. Intertwining aesthetics and politics, these women both rewrite and redesign the parameters of acceptable discourse"--Publisher description.
Introduction: Women, comics, and the risk of representation -- Scratching the surface: 'ugly' excess in Aline Kominsky-Crumb -- 'For all the girls when they have grown': Phoebe Gloeckner's ambivalent images -- Materializing memory: Lynda Barry's One hundred demons -- Graphic narrative as witness: Marjane Satrapi and the texture of retracing -- Animating an archive: repetition and regeneration in Alison Bechdel's Fun home.
Formerly CIP.
boek
Keywords: Kominsky-Crumb, Aline, -- 1948-; Gloeckner, Phoebe; Barry, Lynda, -- 1956-; Satrapi, Marjane, -- 1969-; Bechdel, Alison, -- 1960-